Chemical Constituents and Biological Activities of Essential Oils from Four Species of Bamboo Genus Schizostachyum - Charles Santhanaraju Vairappan; Thilahgavani Nagappan; Liow Ting Hui; Julius Kulip (2015)
Volatile chemical constituents of four species of local bamboo (Schizostachyum blumei Nees., Schizostachyum brachycladum Nees., Schizostachyum lima (Blanco) Merrill and Schizostachyum pilosum S.Dransf.) were investigated. The oils were obtained from bamboo culm through steam distillation and profiled using Gas Chromatography-Mass Spectrometry (GCMS). A total of 59 volatile constituents were identified, and these contained oxygenated sesquiterpene, α-elemol (8.2~21.1 %), coumaran (6.7~32.3 %), guaiacol-4-vinyl (0.6~0.9 %), palmitic acid (1.5~25.6 %), pentacosane (0.1~0.2 %), phytol (1.0~12.6 %), phytol acetate (0.5~1.7 %) and trans-squalene (0.2~1.6 %) consistently in the specimens studied. Based on the observation, S. pilosum exhibited wider diameter of inhibition against Escherchia coli and Staphylococcus aureus compared to the other species of Schizostachyum essential oil.